Assessing the impact of microcredit programs on participant's entrepreneurial behavior: A conceptual framework / Zuraidah Mohamed Isa, Roslan Abdul Hakim and Russayani Ismail - Mohamed Isa, Zuraidah; Abdul Hakim, Roslan; Ismail, Russayani (Penerbit UiTM (UiTM Press), 2015)
Microcredit programs may have an impact on participants 'entrepreneurial behavior. Thus, an understanding of personal attitude, subjective norm and perceived behavioral control as suggested by Ajzen s theory of planned behavior (TPB) may enhance the understanding of the impact of microcredit on participants 'entrepreneurial behavior. Thus, by taking into account the participants 'personal attitude, subjective norm and perceived behavioral control in ways that leads to the enhancement of participants' entrepreneurial behavior, microcredit programs have not only made small loans available to the poor but also helped to enhance entrepreneurial behavior.